SANKSI TERHADAP PERJANJIAN PENETAPAN HARGA (PRICE FIXING) PADA SEKTOR JASA PENGANGKUTAN UDARA (Analisis Putusan KPPU Nomor 15/KPPU-I/2019) - Alya Nurfitriyah; Mustolih Siradj; Indra Rahmatullah (JOURNAL of LEGAL RESEARCH, 2022)
This study discusses the sanctions imposed by the KPPU in the price fixing agreement and how the Commission Council considers the price fixing agreement. This research uses normative legal research, with the research approach used in this study using a statutory approach and a case approach and the data collection method in this research is library research. The results of this study are that the administrative sanctions imposed on the Reported Parties in this decision are only to notify the Business Competition Supervisory Commission in writing before taking any business actor policies that will affect the business competition map. The reported parties should be subject to administrative sanctions in the form of fines. However, due to the ratification of Law Number 11 of 2020 concerning Job Creation, especially Article 48 and also Article 49 concerning additional penalties in this Law, it was removed. Then, according to Article 5 of Government Regulation Number 44 of 2021, especially in paragraph (1) letter c, the Commission Council in deciding this case considered a clear reason, namely the Corona Virus Disease 2019 (COVID-19) Pandemic. So, the Reported Parties in this case were only given administrative sanctions and they were not given. Then, in deciding the case, the Commission Council considered it from the philosophical, sociological and juridical aspects.